Liquid Exfoliated SnP3 Nanosheets for Very High Areal Capacity Lithium‐Ion Batteries. Issue 4 (21st December 2020) - Tian, Ruiyuan; Griffin, Aideen; McCrystall, Mark; Breshears, Madeleine; Harvey, Andrew; Gabbett, Cian; Horváth, Dominik V.; Backes, Claudia; Jing, Yu; Heine, Thomas; Park, Sang‐Hoon; Coelho, João; et al.
Abstract: Increasing the energy density of lithium‐ion batteries requires the discovery of new electrode materials capable of achieving very high areal capacity. Here, liquid phase exfoliation is used to produce nanosheets of SnP3, a 2D material with extremely high theoretical capacity of 1670 mAh g −1 . These nanosheets can be fabricated into solution‐processed thin films for use as lithium storing anodes. To maximize their performance, carbon nanotubes are incorporated into the electrodes to simultaneously enhance conductivity and toughness. As a result, electrodes of thickness >300 µm can be produced, which display active‐mass‐normalized capacities (≈1657 mAh g −1 Active ) very close to the theoretical value. These materials show maximum specific (≈1250 mAh g −1 Electrode ) and areal (>20 mAh cm −2 ) capacities, which are at the state‐of‐the‐art for 2D‐based electrodes, coupled with good rate performance and stability. In combination with commercial cathode materials, full‐cells are fabricated with areal capacities of ≈29 mAh cm −2 and near‐record energy densities approaching 1000 Wh L −1 . Abstract : Liquid phase exfoliation of SnP3 to yield high‐quality nanosheets in reasonable quantities is described. Mixing the nanosheets with carbon nanotubes allows the production of Li‐ion battery anodes with thicknesses of up to 300 µm. Combined with standard cathode materials, these anodes yield Li‐ion cells with extremely high areal capacity and energy density.